Issues and Challenges in Corporate and Capital Market Law Germany and East Asia - Fleischer, Holger; Kanda, Hideki (Mohr Siebeck, 2023)
This volume is based on presentations delivered at a symposium held in March 2016 at the University of Tokyo. It seeks to reinvigorate the scholarly exchange which can be traced back to the late 19th century between company law academics in Germany, China, Japan and South Korea. Contributions from all four jurisdictions include papers on corporate divisions and valuation of shares and its procedure as well as studies on the civil liability of the company and its directors for false financial statements and the corporate law rules on the squeeze-out of minority shareholders.